Pengaruh Kualitas Produk, Daya Tarik Iklan Dan Inovasi Desain Terhadap Loyalitas Pembelian Merek Oppo Di Kota Batam - Eddi; Evyanto, Winda (SCIENTIA JOURNAL, 2025)
This study aims to analyze the effect of product quality, advertising appeal, and design innovation on Oppo brand purchase loyalty in Batam City. This study uses a quantitative approach with a descriptive design. Respondents in this study are Oppo product users in Batam City in 2024, with an unknown number of respondents. Sampling was carried out using the Lemeshow formula with 100 respondents drawn through a purposive sampling method based on certain criteria. The analysis process includes data quality testing, classical assumption testing, influence testing, and hypothesis testing. The results of the study show that product quality contributes 20.2% to purchase loyalty, advertising appeal contributes 33.6%, and design innovation contributes 28.1%. The coefficient of determination (R²) indicates that product quality, advertising appeal, and design innovation together influence purchase loyalty by 83.6%, while the rest is influenced by other factors outside this study. The t-test and F-test show that product quality, advertising appeal, and design innovation have a positive and significant influence on Oppo brand purchase loyalty